A Multi-Objective Goal Programming airport selection model for low-cost carriers’ networks - Chang, Yu-Chun; Lee, Ning (Transportation research. Part E, Logistics and transportation review, 2010)
This paper examines the practicability and validity of the Multi-Objective Goal Programming (MOGP) model in designing a point-to-point airline network. The MOGP mathematical model is used in this study to identify and select a best central airport and its connecting airports providing the best overall optimal performance. By using the proposed model in the selection process, one can expect to achieve the following objectives: (1) an airline network designed at less cost, (2) an airline network that generates more revenues, and (3) an airline network that serves more passengers. Route data from Taipei to the Southeast Asian region were selected for this experiment to validate the model’s practicability.